2019
DOI: 10.1101/19000877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Needs Analysis of Parents Following Sudden Cardiac Death in the Young

Abstract: The sudden cardiac death (SCD) of a young person is a devastating event for any parent. Inherited heart disease is often either identified or assumed to be the cause. Few studies have explored the psychosocial impact to the surviving at-risk family members. We sought to investigate the needs of parents who have experienced the SCD of their child (≤45 years). A quantitative needs analysis questionnaire was developed based on semi-structured interviews, including one focus group, and a review of relevant literat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…First, our results are broadly in line with general observations about the devastating impact of the sudden loss of a child and resulting support needs. 8 As regards the specific challenges of YSCD, our results concur with the recent needs analysis by McDonald et al, 10 which identified needs for instrumental support in the form of a safe place to turn to and emotional support through affiliation and informational input. This is reflected in Theme 1 (YSCD community support as offering a place of safety).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…First, our results are broadly in line with general observations about the devastating impact of the sudden loss of a child and resulting support needs. 8 As regards the specific challenges of YSCD, our results concur with the recent needs analysis by McDonald et al, 10 which identified needs for instrumental support in the form of a safe place to turn to and emotional support through affiliation and informational input. This is reflected in Theme 1 (YSCD community support as offering a place of safety).…”
Section: Discussionsupporting
confidence: 90%
“…This is reflected in Theme 2 (YSCD community support as fostering sense-making). McDonald et al 10 observed that the need for medical information and for understanding the cause of the death constituted the most significant need in families and was mostly unmet. Our study showed that making sense of the death was not only about medical explanations but about meaning-making at a broader level, reflecting definitions of sense-making and meaning-making in the literature on trauma and bereavement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facilitating the “good death,” an obvious priority of care for everyone involved with the dying child, should also be a priority for the health of bereaved families and affected health care providers. 5 McDonald et al 6 analyzed the needs of parents following sudden cardiac death in young ones. They showed that parents' perceived needs for information and support spanned the medical, psychosocial, spiritual, and financial domains.…”
mentioning
confidence: 99%
“…Specifically, they facilitate the processing of the unexpected event, as well as offer meaningful ways to maintain a continuing bond with the deceased (i.e., fundraising for young SCD-related community organizations) [63••]. Additionally, recent evidence describing the multifactorial needs of parents following a young SCD noted that psychosocial needs were the most unmet; more than half (54%) of their parent sample reported psychosocial information and support needs as unfulfilled by the clinical team [64]. As previously shown, proper psychological management may help facilitate post-traumatic growth experiences following the death of a loved one, improving personal strength, resilience, and empathy [60].…”
Section: Scd In the Youngmentioning
confidence: 99%